Effectiveness of Implementing the Lithium Application (Epub Reader) to Reduce Misconceptions on Chemical Equilibrium Material - Dian Rani Minggus; Afadil Afadil; Sitti Rahmawati; Vanny M.A. Tiwow (Department of Chemistry Education, Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2025)
Effectiveness in learning is the achievement of a learning process appropriate and in line with the learning objectives that have been designed, where this success can be achieved because there is a reciprocal relationship between students and educators when learning takes place so that it is able to increase students' interest in participating of learning. The aim of this research is to test the effectiveness of applying the Lithium application to reduce students' misconceptions about Chemical Equilibrium material. The type of research used in this research is research and development (R&D). Research and development is a process carried out to produce a particular product and test the effectiveness of the resulting product. Based on the results of the pretest and posttest for experimental class 1 and experimental class 2, the average percentage results for reducing students' misconceptions in the Chemical Equilibrium material using the Lithium application were 18.3% and 19.4%, respectively. With the N-Gain score level for experimental classes 1 and 2 respectively 0.70 and 0.71 in the High category, while the interpretation of the effectiveness of the N-Gain score for each experimental class is 70.04% and 70, respectively 58% are in the Fairly Effective category.